Clinical efficacy and safety of Cox-maze IV procedure for atrial fibrillation in patients with aortic valve calcification - Guo, Ruikang; Fan, Chengming; Sun, Zhishan; Zhang, Hao; Sun, Yaqin; Song, Long; Jiang, Zenan; Liu, Liming (Frontiers in Cardiovascular Medicine, 2023)
Objective Atrial fibrillation is associated with a high incidence of heart valve disease. There are few prospective clinical research comparing aortic valve replacement with and without surgical ablation for safety and effectiveness. The purpose of this study was to compare the results of aortic valve replacement with and without the Cox-maze IV procedure in patients with calcific aortic valvular disease and atrial fibrillation. Methods We analyzed one hundred and eight patients with calcific aortic valve disease and atrial fibrillation who underwent aortic valve replacement. Patients were divided into concomitant Cox maze surgery (Cox-maze group) and no concomitant Cox-maze operation (no Cox-maze group). After surgery, freedom from atrial fibrillation recurrence and all-cause mortality were evaluated. Results Freedom from all-cause mortality after aortic valve replacement at 1 year was 100% in the Cox-maze group and 89%, respectively, in the no Cox-maze group. No Cox-maze group had a lower rate of freedom from atrial fibrillation recurrence and arrhythmia control than those in the Cox-maze group (P = 0.003 and P = 0.012, respectively). Pre-operatively higher systolic blood pressure (hazard ratio, 1.096; 95% CI, 1.004–1.196; P = 0.04) and post-operatively increased right atrium diameters (hazard ratio, 1.755; 95% CI, 1.182–2.604; P = 0.005) were associated with atrial fibrillation recurrence. Conclusion The Cox-maze IV surgery combined with aortic valve replacement increased mid-term survival and decreased mid-term atrial fibrillation recurrence in patients with calcific aortic valve disease and atrial fibrillation. Pre-operatively higher systolic blood pressure and post-operatively increased right atrium diameters are associated with the prediction of recurrence of atrial fibrillation.